Comparative Analysis of Fecal Microbiomes From Wild Waterbirds to Poultry, Cattle, Pigs, and Wastewater Treatment Plants for a Microbial Source Tracking Approach - Boukerb, Amine M.; Noël, Cyril; Quenot, Emmanuelle; Cadiou, Bernard; Chevé, Julien; Quintric, Laure; Cormier, Alexandre; Dantan, Luc; Gourmelon, Michèle (Frontiers in Microbiology, 2021)
Fecal pollution in coastal areas is of a high concern since impacting bathing and shellfish harvesting activities. Wild waterbirds are non-negligible in the overall signal of the detectable pollution. Yet, studies on wild waterbirds’ gut microbiota focus on migratory trajectories and feeding impact on their shape, rare studies address their comparison to other sources, and developing quantitative PCR (qPCR)-based Microbial Source Tracking (MST) markers to detect such pollution. Thus, by using 16S rRNA amplicon high-throughput sequencing, the aims of this study were (i) to explore and compare fecal bacterial communities from wild waterbirds (i.e. six families and fifteen species; n=275 samples) to that of poultry, cattle, pigs and influent/effluent of wastewater treatment plants (n=150 samples), (ii) and to develop new MST markers for waterbirds. Significant differences were observed between wild waterbirds and the four other groups. We identified 7,349 Amplicon Sequence Variants (ASVs) from the hyper‐variable V3–V4 region. Firmicutes and Proteobacteria, and, in a lesser extent, Actinobacteria and Bacteroidetes were ubiquitous while Fusobacteria and Epsilonbacteraeota were mainly present in wild waterbirds. The clustering of samples in non-metric multidimensional scaling (NMDS) ordination indicated a by-group clustering-shape, with a high diversity within wild waterbirds. In addition, the structure of the bacterial communities was distinct according to bird and/or animal species and families (Adonis R2=0.13; p = 10-4; Adonis R2=0.11; p= 10-4, respectively). The Analysis of Composition of Microbiomes (ANCOM) showed that wild waterbird group differed from the others by the significant presence of sequences from Fusobacteriaceae (W=566) and Enteroccocaceae (W=565) families, corresponding to the Cetobacterium (W=1427) and Catellicoccus (W=1427) genera, respectively. Altogether, our results suggest that some waterbird members present distinct fecal microbiomes allowing the design of qPCR MST markers. For instance, a swan- and an oystercatcher-associated markers (named Swan_2 and Oyscab, respectively) have been developed. Moreover, bacterial genera harboring potential human pathogens associated to bird droppings were detected in our dataset, including enteric pathogens i.e. Arcobacter, Clostridium, Helicobacter and Campylobacter, and environmental pathogens i.e. Burkholderia and Pseudomonas. Future studies involving other wildlife hosts may improve gut microbiome studies and MST markers development, helping mitigation of yet unknown fecal pollution sources.